Mothers’ Knowledge and Practices of Steps to Successful Breastfeeding at Jaramogi Oginga Odinga Teaching and Referral Hospital, Kenya - Agutu, Wycliffe; Situma, Jane; Mutuli, Lucy (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
The ten steps to successful breastfeeding have been reported to be effective in enhancing mothers’ knowledge and practices of breastfeeding in various contexts. However, within the Kenyan context, there is limited literature on mothers’ knowledge and practices regarding these steps despite high breastfeeding-related child morbidity and mortality rates. This study aimed to evaluate mothers’ knowledge, confirm practices of the steps to successful breastfeeding, and establish the relationship between mothers’ knowledge and corresponding practices of these steps. The study site was Jaramogi Oginga Odinga Teaching and Referral Hospital, Kenya. A cross-sectional study design was used, and 79 breastfeeding mothers were systematically sampled. Data were collected through a researcher-administered questionnaire and an observation checklist. Data analysis was performed using descriptive statistics; frequencies and percentages to show mothers’ knowledge and practice distribution. Binary logistic regression was performed to establish a relationship between the two variables. Results were presented in tables. Mothers’ knowledge of steps 3, 6, 7, 8, and 9 met the global criteria for successful breastfeeding; however, only practices of steps 6, 7, 8, and 9 met these criteria. There was no significant relationship between mothers’ knowledge and corresponding practices of all the steps (P>0.05). Skill-based training may be necessary to improve successful breastfeeding practices.